INTEGRASI PENDIDIKAN AGAMA ISLAM DAN ILMU PENGETAHUAN ALAM DALAM PEMBELAJARAN: TINJAUAN SISTEMATIS LITERATUR - Saeful Ahyar, Ahmad; Redho Qurrota A'yun, Ahmad; Hediati, Eti; Septuri; Fauzan, Ahmad (As-Sulthan Journal of Education, 2026)
The integration of Islamic Religious Education (IRE) and Natural Sciences (IPA) is a strategic approach to eliminating the dichotomy of knowledge and shaping students who excel both cognitively and spiritually. This study aims to examine the forms, models, impacts, and challenges of implementing IRE-IPA integration through the Systematic Literature Review (SLR) method using the PRISMA protocol. Data were sourced from Google Scholar, SINTA, and Scopus, yielding 25 relevant articles from the last ten years, which were analyzed using content analysis techniques. The review results indicate that integration is generally implemented by linking cosmic verses (ayat kauniyah) with scientific concepts, instilling monotheistic values in natural phenomena, and applying integrative thematic learning. This practice has been shown to have a positive impact on enhancing understanding of scientific concepts, strengthening religious attitudes, and shaping student character. However, significant challenges were identified, including limitations in teacher competency, a lack of integrative teaching materials, and suboptimal curriculum support. This study contributes a comprehensive mapping of research findings and serves as a conceptual reference for developing integrative learning in schools and madrasas to strengthen the synergy between science and religion.